Taste dysfunction in type 2 diabetes mellitus patients with autonomic neuropathy and its relation with HbA1C level and disease duration - Singh, Archana; Kushwaha, J. S.; Giri, Richa (International Journal of Advances in Medicine, 2022)
Background: Type 2 diabetes mellitus (T2DM) is a multifactorial, complex disease associated with chronic hyperglycemia, resulting from the interplay of genetic, environmental, and epigenetic factors. T2DM can causes various disabling complications. Diabetic autonomic neuropathy (DAN) is one of the common complications in diabetes. The taste threshold affected by various factors such as age, ethnic backgrounds, drugs, local and systemic diseases, consumption of alcohol, smoking, and tobacco chewing. Method: The present study is undertaken with the objectives to compare the taste dysfunction of four primary sensations in Type 2 DM with autonomic neuropathy and its relation with glycemic control. The 60 patients of T2DM with autonomic neuropathy and 60 healthy controls were taken for the study. Autonomic neuropathy was assessed clinically. Chemical taste test using four solutions of basic tastes (sweet, sour, salty, bitter) were done. Results: Taste dysfunction for sweet was significant in T2DM with uncontrolled hyperglycemia. The taste dysfunction in T2DM patients was not related to gender, disease duration, and type of treatment taken. The study found a significant correlation between taste dysfunction, HbA1C level and blood sugar fasting level in T2DM patients. Conclusions: The taste dysfunction was mainly for sweet. Sour and bitter did not show any difference in case groups compared to controls.